Energy, Exergy and Enviroeconomic (3E) analysis of concentrated PV and thermal system in the winter application. (November 2019) - Zuhur, Sadık; Ceylan, İlhan
Abstract: In this study, a Concentrated Photovoltaic/Thermal (CPV/T) air collector has been designed and a prototype is produced. The purpose of this system is to meet the needs of heating and electricity of the building of application in cold winter days. The prototype which has been produced is tested with and without the use of a concentrator. The data which are obtained are exploited to carry out energy, exergy, and environmental cost analyses. During the experiments, while the average outdoor temperature was measured 10°C, the average chamber temperature was measured as 25°C for a system without a concentrator. As for the systems with a concentrator an average chamber temperature of 35°C has been obtained at approximately the same outdoor temperatures. Increasing panel backing temperature has provided a rise in chamber temperatures in winter. With the use of a concentrator, the panel back side temperatures rise and hence the efficiency of electric power production drops with respect to a system that does not employ a concentrator. However, use of a concentrator increases the thermal and electrical energy gains obtained from the system. Overall thermal energy efficiencies for the concentrated and non-concentrated systems approximately equal to 50%. Efficiencies of thermal energy of systems did not exhibit any variations. However, overall thermal energy gain has been calculated as 220 W for a system that employs a concentrator and 136 W for a system that does not.